Patient Management Strategies in Perioperative, Intraoperative, and Postoperative Period in Breast Reconstruction With DIEP-Flap: Clinical Recommendations - Chen, Kuo; Beeraka, Narasimha M.; Sinelnikov, Mikhail Y.; Zhang, Jin; Song, Dajiang; Gu, Yuanting; Li, Jingruo; Reshetov, I. V.; Startseva, O. I.; Liu, Junqi; Fan, Ruitai; Lu, Pengwei (Frontiers in Surgery, 2022)
Background & Objective: DIEP (Deep Inferior Epigastric Perforator) flap is a tissue isolated from the skin and subcutaneous tissue of the lower abdomen or rectus muscle to foster breast reconstruction. The prominent research literature pertaining to the DIEP-flap induced complications in breast reconstruction are limited. Evidence: We conducted a systematic review of the published literature for meta-analysis without a statistical analysis. Information was gathered through internet resources such as PubMed, Medline, eMedicine, NLM, and ReleMed etc. The literature was segregated into a group with literature review and a group for practical meta-analysis. The following key phrases were used for effective literature collection: “DIEP flap”, “Breast reconstruction”, “Patient management”, “Postoperative DIEP”, “Intraoperative anticoagulant therapy”, “Clinical recommendations DIEP”. A total of 106 research papers were retrieved pertaining to this systematic review. Conclusion: A successful breast reconstruction with DIEP-flap without complications is the priority of any surgeon. This study provides evidence-based recommendations on patient management in the perioperative period. The provided recommendations are based on extensive operative experience of surgeons from around the world, who dedicated their life’s work perfectly to execute the art of breast reconstruction surgery with minimal postoperative complications. These recommendations could be beneficial to improve clinical outcomes when performing surgery by minimizing complications in perioperative, intraoperative, and post-operative period.